Development of a facile and bi-functional superhydrophobic suspension and its applications in superhydrophobic coatings and aerogels in high-efficiency oil–water separation. Issue 21 (9th October 2020) - Wang, Xin; Liu, Feng; Li, Yudong; Zhang, Wenbo; Bai, Shunwen; Zheng, Xuelian; Huan, Jinmu; Cao, Guoliang; Yang, Tinghan; Wang, Meng; Jiang, Zishuai; Wang, Chengyu; et al.
Abstract : A superhydrophobic suspension (SH suspension) is an important precursor for the production of superhydrophobic coatings (SH coatings) and sorbents for water-proofing and oil–water separation. Abstract : A superhydrophobic suspension (SH suspension) is an important precursor for the production of superhydrophobic coatings (SH coatings) and sorbents for water-proofing and oil–water separation. However, serious ecological impacts, tedious preparation methods, and low mechanical stability of downstream products significantly hinder the applications of the SH suspension. Herein, a green, facile, and bi-functional waterborne SH suspension fabrication strategy is proposed. Life cycle assessment (LCA) results indicate that the solvent is the primary environmental impact (EI) in 15 categories, indicating the applicability of the as-prepared waterborne SH suspension. By incorporating the hydrophobic nano cellulose fiber (NCF), a low-cost bi-functional SH suspension was then obtained as a precursor for the development of both SH coatings and superhydrophobic nano cellulose fiber (SHNCF) aerogels. These results suggest that the process has high economic viability for high-efficiency oil–water separation. To the best of our knowledge, this study for the first time demonstrates that the use of a waterborne SH suspension incorporated with the NCF (as the frame-structure substrate) and SiO2 (as the modifier to increase roughness, hydrophobicity, BET surface area and pore volume) can largely enhance the mechanical stability of both SH coatings and SHNCF aerogels and lead to low production cost and limited environmental impact. These results can be useful to address the bottlenecks of forming a cost-effective, eco-friendly, and bi-functional SH suspension to meet the real demand.